Performance Enhancement of Areca Sheath Fiber Reinforced Epoxy Composites: Structural Optimization with Polybutylene Terephthalate Monofilaments - Mohamed Adam; Kannapiran Rajendrakumar (Journal of Natural Fibers)
For decades, agricultural waste-derived natural fibers have been explored to reduce plastic waste impacts and improve waste management. However, natural fiber-reinforced composites often underperform compared to high-cost synthetic fibers. This study aims to enhance the performance of areca sheath fiber (ASF)-reinforced epoxy composites through minimal additions (3, 5, and 7 wt%) of low-cost thermoplastic polybutylene terephthalate monofilament (PBTM). The effects of alkali-treated ASF fiber loadings (30, 40, 50, and 60 wt%) and structural modifications on continuous fiber-reinforced composites were examined. PBTM was used to fabricate ASF-reinforced composites with sandwich and random structures. Compared to ASF-reinforced epoxy composites, the sandwich structures increased tensile and flexural strengths by up to 83% and 45%, respectively. Modifying 50 wt% ASF-reinforced composite with 7 wt% PBTM increased the tensile modulus (1.5 to 3.4 GPa), flexural breaking energy (1.1 to 1.7 MJ/m3), and impact strength (24.5 to 36.7 kJ/m2). This modification also significantly enhanced thermal stability and reduced water absorption, as confirmed by thermogravimetric and water absorption analyses. Optical microscopic fractogram characterization indicated that fiber surface treatment improved interface compatibility, while structural modifications of composites enhanced their load-bearing capacity. These findings suggest the suitability of ASF-reinforced PBTM-modified hybrid composites in construction and other structural applications.